HUKUM PENGAMBILAN MANFAAT QARDH TERHADAP PRAKTEK ARISAN UANG PERSPEKTIF IBNU QUDAMAH (Studi Kasus di Desa Gunting Saga Kecamatan Kualuh Selatan Kabupaten Labuhan Batu Utara) - Taufiq Hidayah (Fakultas Syari'ah dan Hukum UIN Sumatera Utara, 2019)
Arisan is a form of contemporary muamalah activity which basically consists of 2 functions, namely as a means for saving and accounts receivable debt. Said to be a means of saving can be seen from the existence of refunds worth the money deposited, while referred to as a means of accounts payable that is due to the existence of parties that owe and owe. The arisan money that applies in Saga Gunting Village, South Kualuh District is the arisan that determines the winner of the participant, the participant will provide meals held at the house of the participant who gets the arisan money. In this money gathering, there is a benefit taking which is a point of concern is the origin of the benefits taken in the money gathering in the form of feeding to other participants, because it is very vulnerable to have an element of qardh benefit taking in it. Qardh in Islam is allowed without any profit taking in the social gathering and does not harm each other, while taking the benefits of the social gathering in the form of meals greatly reduces the results obtained from this money arisan because of those who make the social gathering there are still participants who object to the existence of feeding. The problem in this research is how Ibnu Qudamah's concept of qardh benefit taking law. How is the management of money gathering in Saga Scissors Village and what is the law of qardh benefit taking on the practice of money gathering. The research method used is qualitative descriptive research type analysis through primary data obtained from field research and secondary data obtained from library research. The results showed that the existence of usury in the practice of money gathering. This can be seen from the imbalance between the amount of contributions paid and the amount received due to the use of food costs. Whereas Ibn Qudamah forbade any additional taking or benefits of qardh. Because actually the arisan contract is a qardh contract (accounts receivable). Thus, this money gathering has an element that is forbidden. So to avoid this, cash must be applied for the costs of the meals.